Control strategy of a grid-connected photovoltaic with battery energy storage system for hourly power dispatch - Mohd Aﬁﬁ Jusoh; Muhamad Zalani Daud (Institute of Advanced Engineering and Science, 2017)
The high penetration of ﬂuctuated photovoltaic (PV) output power into utility grid system will aﬀect the operation of interconnected grids. The unnecessary output power ﬂuctuation of PV system is contributed by unpredictable nature and inconsistency of solar irradiance and temperature. This paper presents a control scheme to mitigate the output power ﬂuctuations from PV system and dispatch out the constant power on an hourly basis to the utility grid. In this regards, battery energy storage (BES) system is used to eliminate the output power ﬂuctuation. Control scheme is proposed to maintain parameters of BES within required operating constraints. The eﬀectiveness of the proposed control scheme is tested using historical PV system input data obtained from a site in Malaysia. The simulation results show that the proposed control scheme of BES system can properly manage the output power ﬂuctuations of the PV sources by dispatching the output on hourly basis to the utility grid while meeting all required operating constraints.